2016
DOI: 10.1016/j.virol.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus glycoprotein gM can interact with the cellular protein p32 and knockdown of p32 impairs virus

Abstract: The Epstein-Barr virus glycoprotein complex gMgN has been implicated in assembly and release of fully enveloped virus, although the precise role that it plays has not been elucidated. We report here that the long predicted cytoplasmic tail of gM is not required for complex formation and that it interacts with the cellular protein p32, which has been reported to be involved in nuclear egress of human cytomegalovirus and herpes simplex virus. Although redistribution of p32 and colocalization with gM was not obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…As an important feature, the NEC-associated HCMV protein kinase pUL97 interacts with p32/gC1qR, which bridges pUL97 to the pUL50-pUL53 core NEC [54,58]. A similar bridging function of p32/gC1qR has been suggested for the NECs of other α-, βand γ-herpesviruses [49,55,70,71]. In addition to HCMV pUL97, cellular protein kinases were found to be NEC-associated, in particular, PKC and CDK1 [9].…”
Section: Specific Functional Properties Of Necs and Egress Processes mentioning
confidence: 70%
“…As an important feature, the NEC-associated HCMV protein kinase pUL97 interacts with p32/gC1qR, which bridges pUL97 to the pUL50-pUL53 core NEC [54,58]. A similar bridging function of p32/gC1qR has been suggested for the NECs of other α-, βand γ-herpesviruses [49,55,70,71]. In addition to HCMV pUL97, cellular protein kinases were found to be NEC-associated, in particular, PKC and CDK1 [9].…”
Section: Specific Functional Properties Of Necs and Egress Processes mentioning
confidence: 70%
“…In the case of mass spectrometry-based proteomics analyses performed on HCMV and MCMV, both identical and nonidentical components of their multicomponent NECs have been identified [32,35]. One interesting and consistent finding was the presence of the cellular multi-ligand binding protein p32/gC1qR in α-, βand γ-herpesviral NECs [33,35,40,41]. Our data provided additional evidence that p32/gC1qR is able to interact with HCMV-and MCMV-specific core NEC proteins ( Figure 5 and Figure S1).…”
Section: Discussionmentioning
confidence: 88%
“…p32, as a multiligand-binding, multicompartmental, and multifunctional protein, has been reported to mediate viral nuclear egress through binding to viral proteins (26,33,35). Although previous studies have indicated that p32 can facilitate HSV-1 nuclear egress through interaction with HSV-1 ICP34.5 and UL47 to regulate the rearrangement of the nuclear lamina (25,26), the exact roles of p32 in phosphorylation and rearrangement of lamin A/C remain undefined.…”
Section: Discussionmentioning
confidence: 99%
“…p32 has been reported to be involved in the replication process of various viruses by binding to some specific viral proteins, such as herpes simplex virus 1 (HSV-1) UL47 and ICP34.5 (25,26), human immunodeficiency virus Rev and Tat (27,28), adenovirus core protein (29), hepatitis C virus core protein (30), Epstein-Barr virus (EBV) EBNA-1 (31), and human cytomegalovirus (HCMV) UL97, UL50, and UL53 proteins (32,33). p32 is required for the phosphorylation and redistribution of nuclear lamina during the nuclear egress of HSV-1 via interaction with viral ICP34.5 (26) and has also been implicated in the nuclear egress of HCMV and EBV (33)(34)(35). Interestingly, p32 itself is not a kinase, and the only viral protein with kinase activity that has been shown to be associated with intracellular p32 is human CMV pUL97, which phosphorylates nuclear lamin at the inner nuclear membrane during the process of CMV infection (33).…”
mentioning
confidence: 99%